(3GdJShjb hGdeSDhdjI GdELJeGYjI (B/s - (3GdHcQj, KGeQ jGSQs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2001)
(3GdHYO GdJGQjNj ddeSDhdjI GdELJeGYjI hJYQjagG, eaghe GdeSDhdjI GdELJeGYjI Hjf GdJCjjO hGdeYGQVI, GdJCKjQGJ GdHjFjI Ydi efXeGJ GdCYeGd aj JWHjb GdeSDhdjI GdELJeGYjI, GSJQGJjLjI GdYdGbI Hjf GdJCKjQGJ GdbGfhfjI hGdeSDhdjI GdELJeGYjI, GdJNWjW ddeSDhdjI GdELJeGYjI HEYJeGO GdTcGhi hGdeTcdGJ GdeQJHWI HGdeLJeY, Gdeaghe GdELJeGYj ddJShjb hGdeSDhdjI GdELJeGYjI, MeGjI GdeSJgdc, Mbhb GdeSJgdc, CNdGbjGJ GdJShjb, GdOQGSGJ GdSGHbI aj GdeSDhdjI GdELJeGYjIs
(3HHdjhZQGajG(B: (3U(B.159s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdeSDhdjI GdELJeGYjIs